2020
DOI: 10.2147/opth.s225922
|View full text |Cite
|
Sign up to set email alerts
|

<p>Donor Profile, Tissue Evaluation and Comparison of Voluntary and Motivated Corneal Donation in Nepal Eye Bank</p>

Abstract: Purpose: Corneal problems is one of the major causes of blindness in developing countries like Nepal. This study intended to analyze donor and tissue profile of Nepal Eye Bank (NEB). Material and Methods: This was a cross-sectional descriptive type study. Data of corneal tissues collected by NEB from January 2015 to December 2016 were used in the study. Data collected were demographic profile, cause of death, type of corneal donation (whether voluntary or motivated), quality and utilization of tissues. A compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Co-ordination with law-enforcement agencies and the department of forensic medicine in the institution helps speed up formalities in medico-legal cases, in contrast with the Nepal Eye Bank where such obstacles are met with. [ 33 ] In the present EB, there is proper co-ordination with the other EB in the city to provide required tissues and media when asked for. This is also in contrast to that reported in the North East England study where lack of utilization has been reported after corneas were issued, because the patient was unfit, unavailable, or no longer required the transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-ordination with law-enforcement agencies and the department of forensic medicine in the institution helps speed up formalities in medico-legal cases, in contrast with the Nepal Eye Bank where such obstacles are met with. [ 33 ] In the present EB, there is proper co-ordination with the other EB in the city to provide required tissues and media when asked for. This is also in contrast to that reported in the North East England study where lack of utilization has been reported after corneas were issued, because the patient was unfit, unavailable, or no longer required the transplant.…”
Section: Discussionmentioning
confidence: 99%
“…The latter utilizes 97% of transplantable tissues collected because of equitable country-wide distribution as well as sending of surplus tissues outside the country. [ 33 ] About 68% (34/50) of utilizable corneas were used for optical purposes including penetrating keratoplasty and triple procedure (cataract surgery with corneal replacement, 15/50). This is comparable to a study from the National Eye Bank in the apex institute of this country where optical corneal replacement was performed in about 60% of cases (106/177).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not compare the percentages of non-utilised corneas corneas from the respective collection pool. Bajracharya et al 6 reported a 16.2% discard rate and that poor tissue quality accounted for 11% in their study; motivated donations constituted 87.7%, and tissues were mainly preserved in Cornisol (85%).…”
Section: Discussionmentioning
confidence: 81%
“…7 The high rate of utilization of .69% from previous studies has been attributed to several factors, such as a young donor, lesser death-to-preservation time, and a wellestablished HCRP. [4][5][6] Ranjan et al 4 reported septicemia (n = 56, 30%) as the most common cause of non-utilization, followed by poor tissue quality (n = 55, 30%). Patel et al 5 reported biologic contamination followed by abnormal serology as common causes of non-utilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation